ANALYSIS OF FACTORS AFFECTING ONLINE STORE TAX PAYING COMPLIANCE - Risawati, Risawati (AGUSPATI Research Institute, 2020)
The relatively high costs in terms of taxes, business licenses, and the number of workspaces that support many people to open businesses online from opening a shop or offline. We find many online shops on various social media, for example Facebook, Twitter, Instagram, Line and many others. Quoted from kompas.com, there are no less than 45 million monthly active Instagram users from Indonesia. This fact makes Indonesia the country with the largest Instagram user base in the Asia Pacific. Online shop owners must pay taxes according to regulations set by the government even though they do not have a physical place of business, but the obligation to pay taxes will remain binding. This study aims to examine whether tax knowledge, tax service services, and taxpayer awareness have an effect on online shop owner's tax compliance. The population used is the owner of an online shop in Surabaya on the Instagram site. Data were obtained by distributing questionnaires. carried out using regression analysis, namely classical assumption test, analysis, coefficient of determination, F test and T test. From the results of the analysis and discussion conducted with multiple linear regression analysis, it can be concluded that Tax Knowledge, taxpayer awareness has an effect on Tax Paying Compliance Fiscal services have no effect on tax compliance